2018
DOI: 10.1128/jb.00526-17
|View full text |Cite
|
Sign up to set email alerts
|

Repression of VvpM Protease Expression by Quorum Sensing and the cAMP-cAMP Receptor Protein Complex in Vibrio vulnificus

Abstract: Septicemia-causing produces at least three exoproteases, VvpE, VvpS, and VvpM, all of which participate in interactions with human cells. Expression of VvpE and VvpS is induced in the stationary phase by multiple transcription factors, including sigma factor S, SmcR, and the cAMP-cAMP receptor protein (cAMP-CRP) complex. Distinct roles of VvpM, such as induction of apoptosis, lead us to hypothesize VvpM expression is different from that of the other exoproteases. Its transcription, which was found to be indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Subsequent mass spectrometric analysis of this protein spot revealed SmcR as the potential target protein of QM. SmcR has been recognized as a homologue of LuxR, the quorum-sensing master transcriptional regulator. ,, It has been reported that SmcR activates the expression of vvpE by binding directly to its promoter in the stationary phase. , To confirm direct physical interaction of QM with SmcR, we performed isothermal titration calorimetry (ITC) and showed that QM binds SmcR directly with high affinity ( K D = 0.697 ± 0.013 μM, Figure a). Further we questioned whether this direct binding of QM to SmcR could interfere with its ability to bind to the vvpE promoter.…”
Section: Resultsmentioning
confidence: 73%
“…Subsequent mass spectrometric analysis of this protein spot revealed SmcR as the potential target protein of QM. SmcR has been recognized as a homologue of LuxR, the quorum-sensing master transcriptional regulator. ,, It has been reported that SmcR activates the expression of vvpE by binding directly to its promoter in the stationary phase. , To confirm direct physical interaction of QM with SmcR, we performed isothermal titration calorimetry (ITC) and showed that QM binds SmcR directly with high affinity ( K D = 0.697 ± 0.013 μM, Figure a). Further we questioned whether this direct binding of QM to SmcR could interfere with its ability to bind to the vvpE promoter.…”
Section: Resultsmentioning
confidence: 73%